Mortality among British veterinary surgeons. - Kinlen, L (1983)
A total of 3440 veterinary surgeons resident in Britain were followed up from 1949-53 until 1975. A roughly twofold increase in mortality from suicide was observed and also a decreased mortality from respiratory diseases. There was no excess of deaths from leukaemia or other cancers as recently reported from the United States and as implied by the hypothesis that veterinary surgeons are unusually exposed to oncogenic viruses.